2018
DOI: 10.25288/tjb.358171
|View full text |Cite
|
Sign up to set email alerts
|

Kapadokya Bölgesi (Nevşehir, Orta Anadolu) Kalk-alkalen ve Alkalen Plütonik/ Subvolkanik Kayaçların Petrografik ve Jeokimyasal Özellikleri

Abstract: Akçataş plütonik ve/veya subvolkanik kayaçları ve güneyinde yüzeyleyen Acıgöl Plütonik kayaçları Orta Anadolu Granitoyidleri içerisinde yer alır. Nevşehir'in güneyinde yüzeyleyen Acıgöl plütonu monzogranit bileşimine sahip olup az oranda mafik mikrogranüler anklav (MME) ve iri-K.feldispat megakristalleri içermektedir. Kuzeyde yüzeyleyen magmatik kayaçlar ise monzogranit-kuvars monzonit / monzodiyorit-monzonit-fonolitik tefrit / tefritik fonolit arasında değişen farklı bileşimli kayaçlardan oluşmaktadır. Kuvars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…The Karakaya volcanites, first defined by Metin et al (1987) as 'Karakaya basalt', represent the product of Afyon volcanism, which continues intermittently throughout the lower-middle Miocene, with lava compositions of trachybasalt, basaltic trachyandesite, and trachyandesite. Erkan et al (1996) named the volcanic rocks located north of Afyon as 'northern volcanics' and interpreted these volcanics as lava spills. Aydar (1998) indicated that these lavas are the products of lamproitic magma and explained their formation as lava flows and dikes.…”
Section: Geological Settingmentioning
confidence: 99%
“…The Karakaya volcanites, first defined by Metin et al (1987) as 'Karakaya basalt', represent the product of Afyon volcanism, which continues intermittently throughout the lower-middle Miocene, with lava compositions of trachybasalt, basaltic trachyandesite, and trachyandesite. Erkan et al (1996) named the volcanic rocks located north of Afyon as 'northern volcanics' and interpreted these volcanics as lava spills. Aydar (1998) indicated that these lavas are the products of lamproitic magma and explained their formation as lava flows and dikes.…”
Section: Geological Settingmentioning
confidence: 99%